Typology of Synthetic Forms of the Past Tense of the Verb in the Udmurt Language (Evidentiality and Temporality) - Kirill S. Efimov (Финно-угорский мир)
Introduction. As of today, the grammatical and temporal semantics of the past tense verb forms in the Udmurt language, traditionally designated as “1st past tense” and “2nd past tense”, remain insufficiently studied in academic and scholarly literature. The main difference between these grammatical forms, according to the normative grammars of the Udmurt language, is the presence of an evidential seme in the 2nd past tense. However, information on the nature of the flow of each of the two grammatical tenses, i.e. on the temporal semantics, is missing. The purpose of the research is to identify the meanings expressed by the synthetic forms of the past tense of the Udmurt verb, as well as to specify their similarities and differences.